Implementation of Adaptive Channel Estimation and CIR Sup-port Based on Pilot Arrangement and Adaptive Filtering in MIMO-OFDM Systems - Srinivas, S.; Chandraprakash, T.; sunder, M.Shyam (International Journal of Engineering and Technology, 2018)
OFDM is a promising Technique for achieving high data rates in mobile environment because of its multicarrier modulation technique and ability to convert a frequency selective fading channel into several nearly flat fading channels. The channel estimation techniques for OFDM systems based on pilot arrangement are investigated. The channel estimation based on comb type pilot arrangement is studied through different algorithms for both estimating channel at pilot frequencies and interpolating the channel. In this paper, we initially studied the channel estimation approaches that mainly concentrate on the pilot sequences that have the ability of inserting channel efficiently avoiding interference and maintain orthogonality for OFDM system. However to extend the work, we investigated different adaptive channel schemes namely LMS, RLS and fast RLS. To evaluate the performance of this techniques, the simulations are carried out under Rayleigh channel